ADARp150 counteracts whole genome duplication - van Gemert, Frank; Drakaki, Alexandra; Lozano, Isabel Morales; de Groot, Daniël; Uiterkamp, Maud Schoot; Proost, Natalie; Lieftink, Cor; van de Ven, Marieke; Beijersbergen, Roderick L; Jacobs, Heinz; te Riele, Hein (Nucleic acids research, 2024)
Impaired control of the G1/S checkpoint allows initiation of DNA replication under non-permissive conditions. Unscheduled S-phase entry is associated with DNA replication stress, demanding for other checkpoints or cellular pathways to maintain proliferation. Here, we uncovered a requirement for ADARp150 to sustain proliferation of G1/S-checkpoint-defective cells under growth-restricting conditions. Besides its well-established mRNA editing function in inversely oriented short interspersed nuclear elements (SINEs), we found ADARp150 to exert a critical function in mitosis. ADARp150 depletion resulted in tetraploidization, impeding cell proliferation in mitogen-deprived conditions. Mechanistically we show that ADAR1 depletion induced aberrant expression of Cyclin B3, which was causative for mitotic failure and whole-genome duplication. Finally, we find that also in vivo ADAR1-depletion-provoked tetraploidization hampers tumor outgrowth. Graphical Abstract Graphical Abstract